PENERAPAN DAN PENILAIAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) DI KABUPATEN PURWOREJO DALAM MEMBANTU PENGELOLAAN AKUNTANSI PEMERINTAHAN - Suwandi, Eko Darmawan (P4M STIE Putra Bangsa, 2016)
The purpose of this study was to determine the application and assessment of regional management information systems in Purworejo help the management of government accounting. This study is a qualitative research with this type of case study approach (case study). Case study aims to explore a particular case in more depth by involving the collection of various resources. The results of the research study showed SIMDA application in Purworejo with the accrual system capable manghasilkan information with accuracy or degree of truth better when compared to manual data processing. Assist Leader (Head of Region, the Regional Secretary, as the Budget User Head SKPD) in making decisions appropriate data and information. Internal Control System runs well starting from budgeting, administration until the reporting. Keywords: SIMDA, SKPD, management accounting